2021
DOI: 10.3390/su14010314
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Consumer Health Awareness on Dairy Product Purchase Behavior during the COVID-19 Pandemic

Abstract: Corona Virus Disease 2019 (COVID-19) has led to a reduction in the overall consumption of dairy products in China. How to restore the consumption potential of dairy products and alleviate the serious impact on the dairy market in the post-epidemic period is an urgent problem that needs to be resolved. Based on the survey data of 1780 consumers in 31 provinces (municipalities and autonomous regions) of China, the Heckman two-stage model was used to empirically test the impact of consumer health awareness on dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Improvement of nutritional literacy of the population must also be considered as an effective strategy. It has been shown that increasing the awareness of the consumers positively affects their dairy products consumption [31].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of nutritional literacy of the population must also be considered as an effective strategy. It has been shown that increasing the awareness of the consumers positively affects their dairy products consumption [31].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the study, it was found that there was a significant increase in the general nutrition knowledge (vegetable-fruit, protein foods, whole grains) of primary school students. In another study by Xu et al (2022), the effect of consumer health awareness on consuming dairy products during the pandemic period was investigated. In the study, it was determined that the health awareness of consumers is related to the consumption of dairy products; it was found that if consumer health awareness is high, the purchase of dairy products is also high.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies indicate that increased intake of milk and other dairy products to meet nutritional recommendations can protect against most common chronic diseases, and they have few reported side effects [33]. Dairy products are generally divided into seven categories, but consumers still mainly buy liquid milk [34]. One study recommended increasing dairy consumption by increasing consumer health awareness [34].…”
Section: Product Sustainabilitymentioning
confidence: 99%
“…Dairy products are generally divided into seven categories, but consumers still mainly buy liquid milk [34]. One study recommended increasing dairy consumption by increasing consumer health awareness [34]. There is already enough evidence to proceed with a dietary change that involves switching from dairy products to plant-based alternatives [35].…”
Section: Product Sustainabilitymentioning
confidence: 99%